Associations of Plant- and Animal-Sourced Ultra-Processed Foods and Incident CKD in the Cardiovascular Health Study - Courtney M. Hill; Alyssa Feinberg; Casey M. Rebholz; Rozenn Lemaitre; Amanda M. Fretts; Kerri L. Wiggins; Nona Sotoodehnia; James S. Floyd; Benjamin Lidgard; Nisha Bansal; Bruce M. Psaty; Hyunju Kim (Clinical Journal of the American Society of Nephrology, 2026)
Background: Ultra-processed foods (UPFs) are associated with adverse health. Plant foods can be highly processed. It is not clear whether plant- and animal-sourced UPFs are associated chronic kidney disease (CKD) risk. Methods: Data came from the Cardiovascular Health Study, a prospective cohort of 2,661 older adults (≥65 years). The exposure was UPF intake, classified as plant- or animal-sourced in servings/day using the Nova framework from food frequency questionnaires (1989-1990, 1995-1996). The outcome was incident CKD (estimated glomerular filtration rate [eGFR]